How to spend it: Commodity and non-commodity sovereign wealth funds - Helmut Reisen (Deutsche Bank Research, 2008)
Sovereign wealth funds have become important players in global financial markets. But their investments have repeatedly raised concerns, such as fear of industrial espionage or geopolitical threats. This paper argues that the principal motivation for setting up SWFs should put such concerns into the appropriate perspective. Development economics can explain both the funding sources and the motives that have led to the recent SWF boom, thus helping to prevent the imposition of investment restrictions in OECD countries. The basic principles of public finance and development economics leave little room for conspiracy theories, but draw attention to the fact that funding sources and economic motives differ between commodity and non-commodity SWFs. These principles point to several major motives for countries to build up sovereign wealth funds, rather than merely accumulating official foreign exchange reserves. Foreign exchange reserves can become excessively large, additional economic diversification and efficiency gains can be achieved, technology transfer and network benefits can be fostered, and demographic pressures can be tackled. When using the excess funds, governments have to take important, fundamental decisions. The Hotelling and Hartwick Rules provide theoretical guidance, demonstrating the benefits of transforming oil or other resources into other forms of wealth, rather than consuming them. This not only benefits the investing but also the recipient countries: Protectionism, such as restrictions imposed on SWFs from oil-rich countries, will tend to reduce the risk-adjusted return for oil exporters, and may well contribute to higher oil prices as oil supply is withheld.
Keywords: 330; Staatsfonds; OECD-Staaten